Assessment of the pedestrianization policy in Vigan City UNESCO world heritage site - Amistad, Franklyn T. (American Society of Civil Engineers, 2010)
This study focused on the assessment of pedestrianization policy in Vigan City, a UNESCO World Heritage Site. It aimed to characterize the area and pedestrian movements on implementation of pedestrianization scheme, analyze the perception of respondents on the necessity, acceptability, and impact of pedestrianization scheme, and test the relationships between perceptions and characteristics of respondents. There were 480 respondents chosen randomly. It made use of the exploratory and descriptive method of research. The results showed a very high level of necessity and acceptability of the use of pedestrianization in the city of Vigan. It is recommended that the city government of Vigan should enact an ordinance for the implementation of a ?give way to pedestrians? policy in all the streets in the heart of Vigan City for maximum safety. The city government should also adopt some environmentally sustainable transport strategies in the pursuit of a sustainable development of the city of Vigan without sacrificing its legacy as world heritage site.